PENYULUHAN TENTANG KONDISI FISIK LINGKUNGAN RUMAH DENGAN PENCEGAHAN PENYAKIT TBC DI DESA PAMENGKANG SERANG BANTEN TAHUN 2023 - Ismarina Ismarina; Nurce Arifiati, Prihayati, Marthia Ikhlasiah (JOURNAL OF COMMUNITY DEDICATION, 2023)
Community service activities in the form of counseling are a form of student service to the community through providing empowerment assistance, training, counseling, mentoring and to improve the quality of life. Observations were carried out using interview methods and looking directly into the field. Based on the results of observations and identifying existing problems in Pamengkang Village, Serang, Banten. So one of the work programs was determined, namely "Information Program on the Physical Conditions of the Home Environment with the Prevention of Tuberculosis in Pamengkang Village, Serang, Banten in 2023." Community service activities which started from December 1 2023 - December 14 2023 ran relatively smoothly. Thus, after the community service activities end, it is hoped that the work program that has been provided can be utilized by the workforce and can continue continuously and be maintained to equip themselves as provisions for the future.